Social Engagement and Cognitive Function of Older Adults in Mexico and the United States: How Universal Is the Interdependence in Couples?. (8th June 2021) - Howrey, Bret; Avila, Jaqueline C; Downer, Brian; Wong, Rebeca
Abstract: Objectives: Increased social engagement in older adults has been linked to positive cognitive outcomes; however, it is unclear if the social engagement of husbands and wives influences their own cognition as well as each other's cognition. Moreover, it is unknown if any such patterns persist in different country contexts. Methods: Data from the 2001 Mexican Health and Aging Study (MHAS) and the 2000 Health and Retirement Study (HRS) were combined, and comparable samples of married couples without cognitive impairment at baseline were drawn. Follow-up cognition data was obtained from the 2012 MHAS and the 2012 HRS. Structural equation models (SEM) were used to test the actor–partner interdependence model with moderating effect of country on the association of social engagement with cognition. Results: Significant actor effects were observed for wives in both countries. Actor effects for husbands were observed in the United States only. In Mexico, a significant partner effect was observed where wives' social engagement benefited their own cognition as well as their husbands', but not vice versa. Partner effects were not observed in the United States. No moderation effects of country were observed. Discussion: Our results suggest asymmetric patterns of actor–partner interdependence in Mexico, which may be reflective of the more traditional social role of women, and codependence within the couple. On the other hand, our results for the United States, where each spouse had significant actor effects but no partner effects, may suggest more independence within the couple.